PENINGKATAN KUALITAS PENGURUS POSYANTEK MENJADI SDM YANG UNGGUL DALAM MENYONGSONG ERA INDUSTRI 4.0 - Sigit Purnomo; Rahmi Andini Syamsuddin; Budhi Prabowo; Lili Sularmi; Angga Pratama (LPPM Universitas Pamulang, 2020)
One of the goals of Higher Education Tridharma besides Education and Research is Community Service (Pengabdian Kepada Masyarakat). This is regulated in Articles 20 and 24 of the Law. No. 20 of 2003 concerning the National Education System which states that there is autonomy by Universities, Scientific Research and Community Service. In the implementation we want to develop Appropriate Technology Services (Pelayanan Teknologi Tepat Guna) so that the utilization of PTTG can be accepted by the community by providing guidance, training, mentoring that ultimately the results created are effective and can compete in industry 4.0. Therefore, the management of existing human resources of Posyantek employees is needed to improve competence so that the utilization of Appropriate Technology (TTG) can be understood properly and knowledge of competition in industry 4.0 can be answered effectively and efficiently. We hope that this community service will benefit us all, especially to the young generation of the nation's hopes.Keywords: Human Resources, Posyantek and Appropriate Technology